APPLICATION OF SELECTIVE LASER MELTING IN MANUFACTURING OF FIXED DENTAL PROSTHESES - Dzhendo Dzhendov; Tsanka Dikova (Peytchinski Publishing, 2016)
The additive technologies characterize with the building of one layer at a time from a powder or liquid that is bonded by means of melting, fusing or polymerization. They offer a number of advantages over traditional methods: production of complex personalized objects without the need of complex machinery; manufacturing of parts with dense as well as the porous structure and predetermined surface roughness; controllable, easy and relatively quick process. The methods, mostly used in prosthetic dentistry, include stereolithography, selective laser sintering, and selective laser melting. The aim of the present paper is to review the features of the Selective Laser Melting (SLM) process and the possibilities of its application for production of fixed dental prostheses. The features of the SLM process, the microstructure and mechanical characteristics of dental alloys as well as the properties of fixed dental prostheses, fabricated via SLM, were discussed. It was revealed that the SLM Co-Cr dental alloys possess higher mechanical and tribo-corrosion properties, comparatively good fitting ability and higher adhesion strength of the porcelain comparing to the cast alloys. All this is a good precondition for successful application of the SLM process in the production of fixed dental prostheses, mainly of frameworks for metal-ceramic and constructions covered with polymer/composite, intended for areas with high loading.